2020
DOI: 10.1103/physrevb.102.075423
|View full text |Cite
|
Sign up to set email alerts
|

Highly ordered silicide ripple patterns induced by medium-energy ion irradiation

Abstract: We study the nanopatterning of silicon surfaces under near-normal 40-keV Ar + sputtering with simultaneous Fe oblique codeposition. The ion-beam incidence was kept at 15°, for which no pattern is produced in the absence of metal incorporation. Morphological and compositional analyses were performed by atomic force microscopy, in its morphological and electrical modes, Rutherford backscattering spectrometry, x-ray photoelectron spectroscopy, scanning Auger, as well as transmission and scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
3
7
0
Order By: Relevance
“…It is interesting that, from the very initial stage of the patterning with the emergence of random dots to the development of near-perfect ripple order, both the wavelength and amplitude are retained (see Figures and ). Our observation that the ripples maintain the atomic-scale amplitude throughout the pattern formation is prominent in comparison to previous studies where coarsening of the ripples was generally observed. , , Therefore, we stress that our results indicate not only the stabilization of the ripples at prolonged exposure but more importantly their height is stable on glass surfaces from the very beginning of the structuring process. During irradiation, the only change is the ordering of the ripples, indicating a controllable and atomically precise surface patterning.…”
Section: Results and Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It is interesting that, from the very initial stage of the patterning with the emergence of random dots to the development of near-perfect ripple order, both the wavelength and amplitude are retained (see Figures and ). Our observation that the ripples maintain the atomic-scale amplitude throughout the pattern formation is prominent in comparison to previous studies where coarsening of the ripples was generally observed. , , Therefore, we stress that our results indicate not only the stabilization of the ripples at prolonged exposure but more importantly their height is stable on glass surfaces from the very beginning of the structuring process. During irradiation, the only change is the ordering of the ripples, indicating a controllable and atomically precise surface patterning.…”
Section: Results and Discussionsupporting
confidence: 59%
“…According to the widely accepted linear theory concerning ion-irradiation-induced surface rippling developed by Bradley and Harper (BH), it is the balance between curvature-dependent sputtering that roughens the surface and diffusion that smoothens the surface, leading to the buildup of a regular ripple pattern with a characteristic wavelength. In other generalized theories, nonlinear terms and additional smoothing mechanisms were included. ,, In view of the numerous previous observations involving various materials, the produced ripple patterns have an amplitude of several nanometers or more, and it is rather unlikely that atomic-scale structuring can be achieved because the amplitude will always grow after the initial appearance of the pattern. , , …”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is worth mentioning that similar behaviours were found when medium-energy ion beams were employed for the irradiations [108,120], specifically for a 40 keV Ar + ion beam. In both works, a plate set-up, similar to those used above, was employed.…”
Section: Noble Gas Ion Irradiation With Metal Co-depositionsupporting
confidence: 62%
“…In contrast, at θ = 15 • , an initial disordered dot pattern evolves towards parallel rows of dots. This pattern evolves under further irradiation into a quite ordered ripple pattern [108]. Noticeably, the roughness of the pattern is rather stable and much lower than that produced at θ = 60 • .…”
Section: Noble Gas Ion Irradiation With Metal Co-depositionmentioning
confidence: 85%
See 1 more Smart Citation